The Relationship Between Learning Motivation and Anatomy Practicum Exam Results Among UGJ Faculty of Medicine Students - Hikmah Fitriani; Risnandya Primanagara; Iis Caswati (Green Publisher Indonesia, 2026)
Anatomy is a subject considered difficult by most medical students; therefore, many students obtain unsatisfactory test scores in the anatomy practicum. The anatomy practicum is part of the learning process at the Faculty of Medicine. The learning process is influenced by several factors, including learning motivation. Learning motivation serves as the foundation for students to achieve optimal learning outcomes. The aim of this research was to determine the relationship between learning motivation and the results of the anatomy practicum examination among UGJ Faculty of Medicine students. This study is an analytic observational study with a cross-sectional design. The results of the Spearman correlation test showed that the learning motivation variable and the anatomy practicum scores yielded a value of 0.000 < 0.05, indicating a significant relationship between learning motivation and anatomy practicum examination results. The correlation coefficient was found to be 0.295, indicating that the strength of the relationship between learning motivation and anatomy practicum scores falls into the weak category. The distribution of learning motivation among UGJ Faculty of Medicine students in the anatomy practicum examination showed that 146 students (88%) were in the moderate category, 18 students (10.8%) were in the weak category, and 2 students (1.2%) were in the strong category. Therefore, there is a relationship between learning motivation and the results of the anatomy practicum examination among UGJ Faculty of Medicine students.